Collaboration algorithms between intermediaries for supporting flexible supply chain management - Mohd Tamrin, Mohd Izzuddin; Tengku Sembok, Tengku Mohd; Kartiwi, Mira (North Atlantic University Union, 2013)
The supply chain group consists of members from various locations in the network working together to deliver services to the client. Integration challenges remain as main issue for the group to create more flexible processes and allow modification to be made to the current and global pre-planned processes for the entire supply chain members in the group. The authors introduce Integrative Information Management Architecture (IIMA) running on collaboration algorithms which create semi automated intermediary processes to support management team address integration challenges. The collaboration algorithms are design to go through five main phases in order to continuously monitor and detect any deviations from the processes currently running at the vacinity of the members. The functionalities of existing systems across the members in the group are wrapped and introduce in the IIMA as services. This is to facilitate process restructuring by adding or dropping the required services into the global execution schedule. The authors had develop the prototype of the IIMA and evaluate it with three other related systems in a simulated environment. These systems simulated to support customization processes with common supply chain problems at the beginning and ending stages of that processes. The results demonstrate that the IIMA has the most stable performance in supporting the shared processes when stoke by the problems at both stages of the processes.